Synonymy as a logical philosophical and linguistic category - Semak, Liudmyla; Семак, Людмила Анатоліївна (Дніпровський державний аграрно-економічний університет, 2023)
In scientific research, the phenomenon of synonymy is analyzed from the point of view of logic, philosophy and linguistics. The concept of synonymy in the context of various branches of linguistics is defined. A comparative-historical analysis of the concept of synonymy was carried out. Categorical signs of synonymy have been established. The criteria for establishing synonymous relations between words and concepts are described. The article uses general scientific methods of observation, analysis and synthesis; linguistic methods, among which the traditional descriptive method is used to interpret the essence of the phenomenon of lexical synonymy; a comparative method applied to the analysis of definitions of lexical synonymy. Modern definitions of the phenomenon of synonymy have been elaborated. It is noted that currently linguists have tested several approaches to the study of lexical synonyms in literary texts: linguosemantic, onomasiological, semasiological, linguopragmatic, cognitive and linguistic. It is noted that the study of lexical synonymy in a contextual aspect allows the scientist to gain access to the deep macrostructure of the text. Analysis of language on the subject of lexical synonymy in the plane of discourse and anthropocentrism can be successfully carried out taking into account the actual functional-semantic aspect of synonyms and the communicative features of those communicators who engage in communication itself. It is proved that synonymy is precisely that incredible and incomprehensible linguistic fact, which, on the one hand, is based, most importantly, on the awareness of the similarity/identity of objects, phenomena, concepts of the surrounding reality, and on the other hand, on the search for distinguishing linguistic signs for the nomination of such realities. У наукових дослідженнях явище синонімії аналізується з точки зору логіки, філософії та лінгвістики. Визначено поняття синонімії в контексті різних розділів мовознавства. Проведено порівняльно-історичний аналіз поняття синонімії. Встановлено категоріальні ознаки синонімії. Описано критерії встановлення синонімічних відношень між словами та поняттями. У статті використовуються загальнонаукові методи спостереження, аналізу та синтезу; лінгвістичні методи, серед яких традиційний описовий метод використовується для тлумачення сутності явища лексичної синонімії; порівняльний метод, застосований до аналізу визначень лексичної синонімії. Вироблено сучасні визначення явища синонімії. Зазначається, що нині лінгвістами апробовано декілька підходів до вивчення лексичних синонімів у художніх текстах: лінгвосемантичний, ономасіологічний, семасіологічний, лінгвопрагматичний, когнітивний та лінгвістичний. Зазначається, що дослідження лексичної синонімії в контекстуальному аспекті дозволяє вченому отримати доступ до глибинної макроструктури тексту. Аналіз мови на предмет лексичної синонімії в площині дискурсу та антропоцентризму можна успішно провести з урахуванням власне функціонально-семантичного аспекту синонімів та комунікативних особливостей тих комунікантів, які беруть участь у самій комунікації. Доведено, що синонімія – це саме той неймовірний і незбагненний мовний факт, який, з одного боку, ґрунтується, головне, на усвідомленні подібності/тотожності предметів, явищ, понять навколишньої дійсності, а з іншого – боку, щодо пошуку розрізнювальних мовних знаків для номінації таких реалій.
Синонімія як логіко-філософсько-лінгвістична категорія
Keywords: synonymy; синонімія; lexical synonymy; лексична синонімія; usual synonym; звичайний синонім; contextual synonym; контекстуальний синонім; artistic discourse; художній дискурс